The lock-in - Russell, Bailey J. (Russell, Bailey J. Haunting of Hawthorne Harbor, 2021)
Fifty years after a fire destroyed the town high school, another blaze threatens a group of students participating in a lock-in, leading the teens to further pursue efforts to locate portals that lead to the realm of the dead.